The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1055/s-0030-1269931
|View full text |Cite
|
Sign up to set email alerts
|

Ist eine intramuskuläre Injektion bei autologer Fetttransplantation zur Mamma sinnvoll ? - Eine MRT-volumetrische Studie

Abstract: In autologous fat transplantation to the breast the periglandular plane is superior to the intramuscular plane in terms of volume persistence. As bolus injections of fat tissue must be strictly avoided, the pectoral muscles offer an additional receptor tissue for fat transplantation, and might be especially needed in smaller breasts to achieve the desired volume augmentation. The alternation of glandular tissue within the 2 points of time was low and in relation to the whole region of interest for breast volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 18 publications
(30 reference statements)
0
3
0
1
Order By: Relevance
“…ao injetar a gordura por via intramuscular, a resistência é desproporcionalmente maior, de modo que se pode certamente sentir ao injetar se está sendo injetado por via intramuscular ou periglandular. (7) A comparação dos volumes calculados com a volumetria da RM no pré e pós-operatório revelou uma média de persistência de volume de 64% (± 13%) no músculo peitoral e de 81% (± 8%) na gordura periglandular. (7) No transplante de gordura autóloga para a mama, o plano periglandular é superior ao plano intramuscular em termos de persistência de volume.…”
Section: Resultsunclassified
“…ao injetar a gordura por via intramuscular, a resistência é desproporcionalmente maior, de modo que se pode certamente sentir ao injetar se está sendo injetado por via intramuscular ou periglandular. (7) A comparação dos volumes calculados com a volumetria da RM no pré e pós-operatório revelou uma média de persistência de volume de 64% (± 13%) no músculo peitoral e de 81% (± 8%) na gordura periglandular. (7) No transplante de gordura autóloga para a mama, o plano periglandular é superior ao plano intramuscular em termos de persistência de volume.…”
Section: Resultsunclassified
“…The grow-in rate was 76%, resulting in a net volume increase of the breast of approximately 51.7% of the injected volume. Other authors used MRI to quantify the grow-in rate relative to graft volume with the WAL technique: Herold et al analyzed 10 patients and found an uptake of 77%, 33 and Peltoniemi et al studied 8 patients and found an uptake of 80%. 24 For comparison, various studies evaluated the grow-in rate after fat transfer with techniques other than WAL.…”
Section: Resultsmentioning
confidence: 99%
“…Herold et al found a volume preservation of 81% in the periglandular fatty tissue and a volume preservation of 64% in the muscle at 6 months after the fat cell transplant in a MRIvolumetrically measured series. 33 The pectoralis muscles are thus a possible additional target volume to increase the safely injectable total volume.…”
Section: Reinjectionmentioning
confidence: 99%
“…Autologous fat grafting was performed by one senior surgeon in each center according to the standardized protocol of the BEAULI™ method [65] (see also [21], [22], [64]). The abdomen, waist, back, thighs and upper arms served as donor sites.…”
Section: Methodsmentioning
confidence: 99%